Retail site selection - D.E. Visuals (Firm) (Sunrise, FL. : D.E. visuals, 1994)
Discusses the important considerations for entrepreneurs in selecting retail business sites such as free-standing sites, business- associated sites, and planned shopping centers. Special topics include the principle of cumulative attraction, vacant stores, parking, visibility, leases, and restrictive covenants
Title from title screen
DVD format
Keywords: Store location; Retail trade; Business; Shopping centers